2022
DOI: 10.1097/mpg.0000000000003412
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Magnetic Resonance Index of Activity Is Useful for Terminal Ileal but not Colonic Disease in Pediatric Crohn Disease

Abstract: Background: Ileocolonoscopy (IC) detects mucosal inflammation and magnetic resonance enterography (MRE) detects transmural inflammation in Crohn disease (CD). We aimed to evaluate the relationship between the simplified magnetic resonance index of activity (MARIAs) and measures of inflammation by IC in children with newly diagnosed CD. Methods: Retrospective review of 140 patients 6-18 years of age with CD who had baseline IC and MRE within 5 weeks of diagnosis. MARIAs was calculated for each intestinal segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Interobserver agreement for IUS was higher than MRE in the small bowel for new diagnosis [82% ( k = 0.64)] and for relapsed patients [81% ( k = 0.63)] and in the colon for new diagnosis [64% ( k = 0.27)] and relapsed patients [78% ( k = 0.56)][ 52 ]. Furthermore, a retrospective study in children with IBD demonstrated that MRE is not accurate for the assessment of colonic disease, with the simplified Magnetic Resonance Index of Activity unable to identify severe lesions in colonic segments[ 53 ].…”
Section: Comparison With Other Cross-sectional Imaging Modalitiesmentioning
confidence: 99%
“…Interobserver agreement for IUS was higher than MRE in the small bowel for new diagnosis [82% ( k = 0.64)] and for relapsed patients [81% ( k = 0.63)] and in the colon for new diagnosis [64% ( k = 0.27)] and relapsed patients [78% ( k = 0.56)][ 52 ]. Furthermore, a retrospective study in children with IBD demonstrated that MRE is not accurate for the assessment of colonic disease, with the simplified Magnetic Resonance Index of Activity unable to identify severe lesions in colonic segments[ 53 ].…”
Section: Comparison With Other Cross-sectional Imaging Modalitiesmentioning
confidence: 99%
“…Both IUS and MRE have a high sensitivity for detecting small bowel Crohn disease (CD) activity with substantial practitioner agreement for the presence of active ileal inflammation. This suggests that both modalities are valid tools for disease activity assessment, supporting the use of IUS as an accurate tool for serial monitoring during routine exam visits (6–9). Presently, there is a lack of standardized approach to bedside IUS among gastroenterologists.…”
mentioning
confidence: 99%
“…The Magnetic Resonance Index of Activity (MaRIA) and simplified MaRIA (sMaRIA) index have become excellent tools for monitoring transmural inflammation in adults with CD, but are limited by the need for rectal contrast and real-world accuracy in children with CD. [4][5][6] In turn, the development of the Pediatric Inflammatory Crohn's Magnetic Resonance Enterography Index (PICMI) has the potential to be transformative, filling a critical need for pediatric patients with CD, becoming the first validated cross-sectional imaging scoring system in children to discriminate transmural disease activity at a single time point. PICMI has the ability to measure treatment responsiveness and healing, that is both accurate and without the need for rectal contrast.…”
mentioning
confidence: 99%